Consolidation out of Diversification in Narratology (ENTHYMEMA, 2013)
Although the field of narratology is increasingly diversified with the appearance of various new approaches and new models, it has more elements of consolidation than the picture appears to be. I will discuss three aspects of consolidation: (1) how postclassical narratologies consolidate classical narrative poetics; (2) how the cognitive approach to unreliability consolidates the rhetorical criterion of unreliability and, moreover, how the rhetorical approach consolidates the cognitive concern with individual readers; and (3) how the Chinese classification of modes of discourse presentation consolidates its Western counterpart.
Keywords: Narratology; consolidation; diversification